2017
DOI: 10.1038/s41598-017-05379-w
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MD1 exacerbates pressure overload-induced left ventricular structural and electrical remodelling

Abstract: Myeloid differentiation protein 1 (MD1) has been implicated in numerous pathophysiological processes, including immune regulation, obesity, insulin resistance, and inflammation. However, the role of MD1 in cardiac remodelling remains incompletely understood. We used MD1-knockout (KO) mice and their wild-type littermates to determine the functional significance of MD1 in the regulation of aortic banding (AB)-induced left ventricular (LV) structural and electrical remodelling and its underlying mechanisms. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 66 publications
(72 reference statements)
6
45
0
Order By: Relevance
“…In addition, alterations in Ca 2+ handling proteins in WT‐Aldo mice were significantly worsened in KO‐Aldo mice. A recent study indicated that MD1‐KO can interfere with the expression of Ca 2+ handling proteins in pressure‐induced HF mice . Therefore, there is strong and growing evidence that MD1 deletion worsens the dysregulation of calcium handling and increases the vulnerability of aldosterone‐induced HFpEF mice to AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, alterations in Ca 2+ handling proteins in WT‐Aldo mice were significantly worsened in KO‐Aldo mice. A recent study indicated that MD1‐KO can interfere with the expression of Ca 2+ handling proteins in pressure‐induced HF mice . Therefore, there is strong and growing evidence that MD1 deletion worsens the dysregulation of calcium handling and increases the vulnerability of aldosterone‐induced HFpEF mice to AF.…”
Section: Discussionmentioning
confidence: 99%
“…The MD1‐RP105 complex can directly interact with the MD2‐TLR4 complex by lateral binding, acting as a negative physiological regulator of the TLR4 signalling pathway . Our previous study showed that MD1 is widely expressed in the heart, and MD1 deletion leads to a more pronounced activation of the TLR4/CaMKII signalling pathway, which may further significantly influence the expression levels of Ca 2+ handling proteins, increasing the vulnerability of HF mice to ventricular arrhythmia . Therefore, we hypothesized that MD1 deletion can alter calcium homoeostasis in atrial myocytes and increase susceptibility to AF in HFpEF by enhancing the activation of TLR4/CaMKII signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that MD1 expression was downregulated in heart failure patients [6,7], and loss of MD1 could worsen structural and electrical remodeling under pressure overload and ischemia/reperfusion injury conditions via increased the activation of the TLR4 signaling pathway [6,8]. Interestingly, we also found that MD1 deletion had no significant effect on the cardiac structure in wild-type (WT) mice under physiological conditions [6][7][8][9][10][11]. Moreover, downregulated MD1 does not activate the TLR4 signaling pathway in both in vitro and in vivo experiments [7,9].…”
Section: Introductionmentioning
confidence: 96%
“…The MD1-RP105 complex can directly interact with the myeloid differentiation protein 2 (MD2)-Toll-like receptor 4 (TLR4) complex by a lateral binding, acting as a negative physiological regulator of the TLR4 signaling pathway [5]. Our previous studies found that MD1 expression was downregulated in heart failure patients [6,7], and loss of MD1 could worsen structural and electrical remodeling under pressure overload and ischemia/reperfusion injury conditions via increased the activation of the TLR4 signaling pathway [6,8]. Interestingly, we also found that MD1 deletion had no significant effect on the cardiac structure in wild-type (WT) mice under physiological conditions [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, they may be implicated in neuronal injury in response to I/R or oxygen-glucose deprivation/reoxygenation (OGD/R) insult with respect to inflammation, apoptosis and ROS (7,8). RP105 is a member of the TLR family and acts as an endogenous inhibitor of TLR4, regulating acute/chronic myocardial ischemia and pressure overload-induced cardiac remodeling (9)(10)(11). Although the benefits have been well established for RP105 with regard to dependence on TLR4-limited patterns, data since has shown the effects of RP105 in TLR4-independent approaches (10).…”
Section: Introductionmentioning
confidence: 99%